2008
DOI: 10.1097/sih.0b013e31815f0d51
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students Learn Over Distance Using Virtual Reality Simulation

Abstract: These findings suggest the feasibility and acceptability by students in the use of VR simulation integrated into a PBL learning session, as well as multipoint distance technologies that allowed interaction between students and tutors in different locations. The authors believe that these modalities can be applied where students and tutors from different institutions are in separate locations and can be used to support interactive experiential learning in a distributed network or on site and suggest areas for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 9 publications
0
25
0
1
Order By: Relevance
“…Of the 4 remaining Web-based IPSs, 1 was already presented in 2003 and uses a custom-made 3D world. Again, the key aspect of the simulator is a feasibility study, in this case particularly with regard to distance learning [ 19 , 24 ]. The 3 remaining Web-based IPSs were built by commercial software companies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 4 remaining Web-based IPSs, 1 was already presented in 2003 and uses a custom-made 3D world. Again, the key aspect of the simulator is a feasibility study, in this case particularly with regard to distance learning [ 19 , 24 ]. The 3 remaining Web-based IPSs were built by commercial software companies.…”
Section: Resultsmentioning
confidence: 99%
“…Alverson et al (2008) conducted an evaluation of interactive problem solving using text-based and VR-integrated exercises with students in New Mexico and Hawaii. They found that the VR component could be successfully incorporated into the live training sessions over these distances.…”
Section: Immersive Vr Collaborative Training Systemsmentioning
confidence: 99%
“…8 Others are under development, including training programs using simulation and, distributed virtual reality. [9][10][11][12][13][14][15][16] Current efforts are aimed at exploring the integration of other HIT efforts with telehealth in coordination with LCF Research (http:// www.lcfresearch.org/) and their statewide HIE called the New Mexico Health Information Collaborative, as well as the Health Information Regional Extension Center, fostering adoption of electronic health records among primary care providers and helping them to achieve meaningful use.…”
Section: Description Of Context Setting and Role Of Telemedicine Wimentioning
confidence: 99%